Perpindahan Kalor Konveksi Piringan Berputar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Heat transfer on a rotating disk has been investigated experimentally. It was intended for simulating heat transfer on a disk brake. The principle of heat-mass transfer analogy was used for estimating the heat transfer coefficient. The rotating disk was made of naphthalene with various outer diameters - innter diameter ratio of 4, 3, 2, and 1.3. The results was presented as nondimensional equation v 1%14 (d )0,23 Nu := 0,573(Re)0.63(T3